766. Migration Flows and Increase of Extrapulmonary Tuberculosis in a Low Prevalence Setting: A Retrospective Analysis in Two Italian Centers. (26th November 2018) - Compagno, Mirko; Campogiani, Laura; Coppola, Luigi; Sarmati, Loredana; Andreoni, Massimo; Francisci, Daniela; Saraca, Lavinia; Baldelli, Franco
Abstract: Background: Extrapulmonary tuberculosis (EPTB) represents 25% of Worldwide tuberculosis and it is more commonly associated with immunodepression. The purpose of this study was to determinate the burden of EPTB in a low TB prevalence setting. Methods: A retrospective evaluation of patients treated for TB at Tor Vergata Hospital and Terni Hospital (Italy) from January 2013 to November 2017 was done. Clinical charts, laboratory tests and radiological findings were reviewed and analysed. Data were elaborated using Yates' method analysis, Fisher test and Pearson's chi-square test. Results: A total of 171 patients were enrolled from 2013 to 2017 in two Italian centers (Rome and Terni); 71% were males, with a mean age of 41.5 years. The number of TB diagnosis increased among the study period (6.6% in 2013 vs. 56% in 2017) and an increase of EPTB (23% in 2013 vs. 44% in 2017) was seen. Most commonly EPTB presented as generalized lymphadenitis (34%), osteomyelitis and spondylodiscitis (28%) and other sites localizations (31%). Statistical analysis revealed a significant correlation between geographical provenience and TB localization ( P = 0.004). Extra European immigrants (76% Africans) resulted at higher risk of EPTB (OR 2.31; CI 95% 0.63–8.46), while being Caucasian showed a protective role toward EPTB development ( P = 0.001). The risk of EPTB doubled in 2015–2017 respect 2013–2014. Conclusion: From 2013 to 2017 an increase in TB admissions was documented with a significant higher number of EPTB cases, particularly in extra-European immigrants. The doubled risk in 2015–2017 was likely the consequence of the recent ongoing escalating levels of migration from African countries and may result as an emerging Public Health problem. Disclosures: All authors: No reported disclosures.